Pengukuran Kebutuhan untuk Perancangan Intervensi Sosial dan Penurunan Resiko Tindak Kekerasan dalam Keluarga di Daerah Istimewa Yogyakarta - Wimbarti, Supra (Faculty of Psychology, Universitas Gadjah Mada, 2006)
Marital abuse on woman is not new concept, but it seems like iceberg which is only its top that is shown and most of it’s body are not. This research covers marital abuse on woman that includes physical and also psychological. The purpose of this research is focused on exploration about the proper way to solve marital abuse and coping behavior that women choose. The findings show that there are 13 kinds of abusive behavior including physical abuse and psychological abuse. 19% of marital abuse cases happen in last year. This research also shows that wife’s response against the abuse are silence, crying or asking their husband about the reason. On the other hand, help-seeking behavior is also shown by the wifes. Keywords: Marital abuse, coping behavior